PENGARUH PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI TERHADAP PERILAKU KESEHATAN WANITA LESBIAN DI KOTA BANDUNG - Rhomadona, Shinta Wurdiana (D3 Kebidanan, 2013)
The aim of the study is to find how the effect of knowledge and attitudes about reproductive health of health behavior to lesbian women,s in Bandung city.The method in this study is analytic with cross sectional study design. The data used are primary data of questionnaire distributed to 75 women lesbians in Bandung city. The data analysis used rank spearmant.The results of this study show that the knowledge and attitude about reproductive health is significantly influences the health of lesbian women in Bandung city with the contribution of the influence of knowledge of 22,45%. While the attitudes influence is13,46 %.The conclusion of this study is the knowledge and attitudes about reproductive health give a significant influence on health behavior to lesbian women in Bandung city.Key words : Attitude, Health Behavioral, Knowledge, Reproductive Health